"Couchsurfing has made me a better person and the world a better place": the transformative power of collaborative tourism experiences. Issue 1 (2nd January 2018) - Decrop, Alain; Del Chiappa, Giacomo; Mallargé, Jérôme; Zidda, Pietro
ABSTRACT: Presented as an alternative form of tourism, Couchsurfing is a predominantly non-commercial accommodation type where hosts offer a "couch" to travelers through a hospitality network. Couchsurfing.com is considered as an icon of the sharing economy and more specifically of shareable tourism. This article provides a deeper understanding of couchsurfers' motivations and shared values. Through an empirical qualitative study, we discuss the transformative power of Couchsurfing experiences, the underlying transformational processes, conditions, and socio-psychological and behavioral consequences. We also discuss the findings' implications for society, businesses, and tourism in general.